Hubungan Pengetahuan Mahasiswa Keperawatan Universitas Awal Bros dengan Efikasi Diri Tentang Perawatan Paliatif - Dinda Rizki Rhamadhan; Siska Natalia; Rizki Sari Utami Muchtar (Inovasi Kesehatan Global, 2025)
The World Health Organization (WHO) reported in 2019 that 40 million people worldwide require palliative care, including those with cardiovascular disease (38%), cancer (34%), chronic lung disease (10.3%), AIDS (5.7%), and diabetes (4.6%). Palliative care aims to improve the quality of life of patients and families facing life-threatening illnesses by managing pain and physical, psychological, social, and spiritual problems. The main goal of this care is to reduce suffering and help patients cope with the limitations imposed by illness. The principles are to respect life, consider death a normal process, neither hasten nor delay death, and provide support until the end of life. This study aims to determine whether knowledge can influence the level of self-efficacy of nursing students at Awal Bros University. Using a correlational quantitative method, data were collected through the Palliative Care Quiz for Nursing and Self-efficacy Palliative Care Scale questionnaires. The results of the study show a significant relationship between knowledge and self-efficacy among students with p<0.005. These findings can be used as a basis for learning to improve the understanding of nursing students, especially in the context of palliative care, which is important for the quality of health services in the future.